2015
DOI: 10.1093/toxsci/kfv119
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotoxic Effect of 13,19-Didesmethyl and 13-Desmethyl Spirolide C Phycotoxins Is Mainly Mediated by Nicotinic Rather Than Muscarinic Acetylcholine Receptors

Abstract: Spirolides are a large family of lipophilic marine toxins produced by dinoflagellates that have been detected in contaminated shellfish. Among them, 13,19-didesmethyl and 13-desmethyl spirolide C phycotoxins are widely distributed and their mode of action needs to be clearly defined. In order to further characterize the pharmacological profiles of these phycotoxins on various nicotinic acetylcholine receptor (nAChR) subtypes and to examine whether they act on muscarinic receptors (mAChRs), functional electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 51 publications
7
34
0
Order By: Relevance
“…It has been found that, on isolated frog or mouse neuromuscular preparations, gymnodimine A induces a reversible time- and concentration-dependent blockage of twitch tension responses evoked by nerve stimulation without affecting directly-elicited muscle twitches. 94 Similar effects were later observed with 13-desmethyl spirolide C 95 and pinnatoxin F, with the latter toxin causing a complete abolition of the rat hemidiaphragm action potential responses evoked by nerve stimulation, while no effect was observed after an electrical stimulation. 96 In addition, gymnodimine A blocks the miniature endplate potential in frog and mouse isolated neuromuscular preparations.…”
Section: Biological Activity and Modes Of Actionsupporting
confidence: 58%
“…It has been found that, on isolated frog or mouse neuromuscular preparations, gymnodimine A induces a reversible time- and concentration-dependent blockage of twitch tension responses evoked by nerve stimulation without affecting directly-elicited muscle twitches. 94 Similar effects were later observed with 13-desmethyl spirolide C 95 and pinnatoxin F, with the latter toxin causing a complete abolition of the rat hemidiaphragm action potential responses evoked by nerve stimulation, while no effect was observed after an electrical stimulation. 96 In addition, gymnodimine A blocks the miniature endplate potential in frog and mouse isolated neuromuscular preparations.…”
Section: Biological Activity and Modes Of Actionsupporting
confidence: 58%
“…909 Electrophysiological and competiton binding experiments have identied that 13-desmethyl spirolide C is a potent but relatively non-selective ligand of nAChRs while 13,19-didesmethyl spirolide C is more selective of the muscular-type receptor. 910 Both MNPs interacted weakly with muscarinic AChRs. Further investigation of the unusual occurrence of tetrodotoxin in New Zealand collections of the nudibranch Pleurobranchaea maculata has led to the metabolite being detected in mucin cells, the mantle, gonad tissue and the digestive gland of the nudibranch as well as in the larvae and eggs but not in the gelatinous egg cases.…”
Section: Molluscsmentioning
confidence: 99%
“…), 13‐desmethyl spirolide C and 13,19‐didesmethyl spirolide C (Aráoz et al . ), 20‐methyl spirolide G (Couesnon et al . ), and pinnatoxins E, F, and G (Hellyer et al .…”
Section: Mode Of Action On Muscle‐type Nachrsmentioning
confidence: 99%
“…), 13‐desmethyl spirolide C and 13,19‐didesmethyl spirolide C (Aráoz et al . ), and pinnatoxins E, F, and G (Hellyer et al . ), either reduced or completely blocked (depending on concentration) the amplitude of spontaneous miniature endplate potentials, an effect suggesting that the toxins impeded the interaction of ACh quanta with endplate nAChRs.…”
Section: Mode Of Action On Muscle‐type Nachrsmentioning
confidence: 99%